ANALISIS KRITERIA PERSONAL BRANDING SELEBGRAM NON SELEBRITI (STUDI DESKRIPTIF KUALITATIF AKUN INSTAGRAM @LIPPIELUST) - Dita Rachmawati; Dini Salmiyah Fithrah Ali (Jurusan Ilmu Komunikasi UTM, 2018)
Social media nowadays has become tool of marketing and promotion of goods, services, and personal like Instagram. Being a celebgram should have a strong Personal Branding, has uniqueness, the difference from other celebgram in order to have a long existence to be celebgram on social media Instagram. Rissa is a non-celebrity celebgram. Rissa’s known as an endorser for beauty project this leap how to work together on a project professional with many brands in the country and abroad. Rissa became a celebgram with a very specific focus that is more beauty that leads to lipstick. This study analyze about how Personal Branding criteria non celebrity celebgram. The method used is descriptive qualitative with indicator 11 Authentic Personal Branding criterion according to Rampersad. In this study, Rissa’s Personal Branding has a personality as which is character, values, vision that suits personal ambition, moral code and behavior, consistent, focused on one field, acknowledged and experienced, unique, connected to the audience, owns good relationship with partner work and always make self improvement in Instagram account @ lippielust.